Investigation on the microstructure development and corrosion performance of friction stir welded dissimilar AZ31/AZ91 magnesium alloys - Nurul Shuhada, Haji Mohamed (2020)
Magnesium (Mg) and its alloys are attractive alloys for automotive industries and electronic devices due to their lightweight properties. Based on the potential of Mg alloys as parts and components for weight reduction, it could contribute to eco-friendly materials due to the reduction of carbon dioxide (CO2) emission by the usage of the lightweight materials. Friction stir welding (FSW) is a solid-state joining method that can resulted an effective microstructure refinement useful for thin Mg sheets. During FSW, the material is soften without melting and by maintaining low temperature, good quality joints can be produced with significant low residual stresses. The parameters of FSW, such as tool rotational speed and welding speed exert a significant effect on the material flow pattern and temperature distribution, thereby influencing the microstructural development of a material. The rapid degradation rate of Mg alloys in most environments has seriously limited their growth in automotive applications due to the position in the electromotive force (EMF) and galvanic series in seawater. The aims of this study are to investigate the microstructure development of friction stir welded Mg alloys by highlighting the effect of various tool rotational speed on the microstructure of Mg Alloys and also to evaluate the corrosion performance of friction stir welded Mg alloys by correlating to the microstructure development. The joining of dissimilar AZ31 and AZ91 Mg alloys was successfully conducted by FSW and defect-free joints with recrystallized grain structure were achieved. Tool rotational speed and welding speed were varied during FSW, and the microstructures of joint samples were characterized by optical microscopy (OM) and scanning electron microscopy (SEM). The corrosion behaviour of each sample was evaluated by hydrogen evolution test and electrochemical measurement by potentiodynamic polarization test. Each region of the welded sample, namely the heat-affected zone (HAZ), the thermomechanical heat-affected zone (TMAZ), the stir zone (SZ), and the base metal (BM) formed by the welding process represented a clear grain size variation. Based on the observation, homogeneous grain structure occurred at most of the regions, and the SZ was determined as the region with the most grain refinement compared to other regions. Increasing the tool rotational speed from 800 to 1,000 and 1,200 rpm showed no significant changes on grain size. The Vickers hardness values at the SZ are 70 to 100 HV due to recrystallized small grain structure produced by FSW. The reduction of rotational speed from 1,200 to 800 rpm contributed to the variation of corrosion resistance during hydrogen evolution test in 3.5 wt. % of sodium chloride (NaCl) solution. The welded Mg alloys exhibited open circuit potential (OCP) values in the range of -1.624 to -1.58 V. The potentiodynamic polarization curve indicated the increase of corrosion rate with the decrease of welding speed from 1,200 to 800 rpm as evidenced by the current density (icorr) values. In conclusion, by considering the homogeneous grain structure, grain refinement, and presence of aluminum-manganese (Al-Mn) intermetallic, the corrosion rate and electrochemical behavior changed in different regions, which contributed to the overall corrosion performance of the welded Mg samples. This study is recommended as a solution on proper joining technique and corrosion performance of dissimilar Mg alloys.